PENGARUH YOGA KEHAMILAN TERHADAP KECEMASAN DAN LAMA PERSALINAN KALA I DI KOTA PEKANBARU - Eva Santi Hutasoit; Susani Hayati (JOMIS (Journal of Midwifery Science), 2021)
Women who are currently pregnant experience many changes. Changes in body and mind can cause discomfort to pregnant women. In addition to physical discomfort, psychological discomfort is also common. Anxiety and depression in pregnancy are problems with a high prevalence. One of the interventions that can reduce anxiety can be physical exercise such as yoga. Yoga can reduce stress, improve quality of life, self-efficacy in childbirth, interpersonal relationships, autonomic nervous system function, provide comfort, reduce or decrease labor pain and shorten the duration of labor. The purpose of this study was to analyze the effect of pregnancy yoga on anxiety and the duration of the first stage of labor in the city of Pekanbaru. This type of research is an observational study with a case control design. This research was conducted in 5 maternity homes in Pekanbaru City with a total sample of 96 respondents. The Zung-Self Rating Scale (ZSRS) questionnaire data collection tool and the first stage of labor using a questionnaire. Bivariate data analysis using chi-square calculations. The results of the Chi-square statistical test for anxiety variables showed a p value of 0.000 <0.05 (95% CI), there was a relationship between anxiety status and pregnancy yoga exercises. The variable of the first stage of labor showed a p value of 0.013 <0.05 (95% CI), there was a relationship between the first stage of labor and pregnancy yoga exercises. The effect of yoga exercises can reduce anxiety levels and shorten the first stage of the active phase of labor. It is hoped that health workers, especially midwives, can increase the frequency of providing information about pregnancy yoga and the frequency of implementing yoga exercise classes, both at RB and other health facilities.